Enhanced performance of the Milan System for Reporting Salivary Gland Cytopathology: Point of view from an Asian country. Issue 5 (5th February 2020) - Higuchi, Kayoko; Urano, Makoto; Nakaguro, Masato
Abstract : In this issue of Cancer Cytopathology, Lee et al describe their experience with the Milan system in Singapore in a retrospective study over 10 years. Diagnosing lymphoid lesions and Warthin tumors is often a challenging issue in salivary gland fine needle aspiration cytology.